Preparation of a Composite Scaffold from Polycaprolactone and Hydroxyapatite Particles by Means of Alternating Current Electrospinning - Jirkovec, Radek; Holec, Pavel; Hauzerova, Sarka; Samkova, Alzbeta; Kalous, Tomas; Chvojka, Jiri (ACS omega, 2021)
This research involved the production of polycaprolactone fiber layers via the alternating current electrospinning method. To construct the micro/nanofiber scaffold, mixtures of two molecular weight solutions, M n 45 000 and M n 80 000, were spun in differing proportions in a solvent system containing acetic acid, formic acid, and acetone in a ratio of 1:1:1. The composite fiber materials with hydroxyapatite particles were prepared from a solution that combined the different molecular weight solutions at a ratio of 1:3. The study resulted in the preparation of fiber layers containing 0, 5, 10, and 15% (wt) hydroxyapatite particles from the dry mass of the polycaprolactone. The strength, wettability, and surface energy of the composite materials were examined, and the results demonstrated that hydroxyapatite affects the fiber diameters, strength, and surface energy and, thus, the wettability of the fiber layers. The fibrous layers produced were further tested for cytotoxicity and cell viability and proliferation. The results obtained thus strongly indicate that the resulting bulky micro/nanofiber layers are suitable for further testing with a view to their eventual application in the field of bone tissue engineering.